Cover Picture: Using Time‐Dependent Density Functional Theory to Probe the Nature of Donor–Acceptor Stenhouse Adduct Photochromes (ChemPhysChem 12/2016). Issue 12 (6th June 2016) - Laurent, Adèle D.; Medveď, Miroslav; Jacquemin , Denis
Abstract : The Front Cover picture illustrates the recently developed DASA photochromes, which are investigated with refined ab initio tools and the ground and excited‐state properties of both forms are rationalized. More information can be found in the Full Paper by D. Jacquemin and co‐workers onpage 1846 in Issue 12, 2016 (DOI:10.1002/cphc.201600041 ).